Estimation of psychological features, body composition and status of actual nutrition of women with eating behavior disorders - Olga V. Filatova; Sergei S. Polovinkin; Irina V. Chervova; Evgenia I. Baklanova; Irina O. Plyasova (Ожирение и метаболизм, 2018)
Background: the violations of eating behavior began to be actively studied since the mid-20th century. In recent years, researchers from different countries have found new evidence of the role of eating behavior, the patient's eating habits in the development of obesity. Since the scope of the study of eating behavior and its disorders began to develop actively relatively recently, many aspects of this problem have not yet been studied. Aim: was to study the psychological features, body composition and parameters of actual nutrition of women with eating behavior disorders. Methods. We used the Dutch questionnaire DEBQ to analyze the types of eating behavior. To assess the severity of eating disorders inherent in eating disorders, the technique "Scale of Eating Behavior Assessment" was used. The actual mental state of the subjects was studied using a clinical and psychological test – a questionnaire of the severity of psychopathological symptoms (SCL-90-R). The component composition of the body was assessed using the apparatus for bioimpedanceometry ABC-01 "Medass". The evaluation of the actual nutrition by the method of frequency analysis was carried out with the help of the computer program "Analysis of the state of human nutrition". Results. In all groups of women with eating disorders, higher values on the scales of desire for thinness, bulimia and dissatisfaction with the body, somatization, obsessional-compulsiveness, interpersonal sensitivity, depressiveness, anxiety were found. As the eating disorders worsened, the consumption of mono-and disaccharides and added sugar increased, which was accompanied by an increase of the body fat, both in absolute and relative units. Conclusions. In women with eating disorders violations of personal and psychological characteristics, nutrition patterns were detected, which were accompanied by an increase in body fat.